Exploring the heterogeneity and nonlinearity of trade-offs and synergies among ecosystem services bundles in the Beijing-Tianjin-Hebei urban agglomeration - Shen, Jiashu; Li, Shuangcheng; Liang, Ze; Liu, Laibao; Li, Delong; Wu, Shuyao (Ecosystem services, 2020)
•Six ecosystem services (ESs) and the relationships among them were analysed.•The relationships among the same types of ESs differed in different bundles of ESs.•Trade-offs and synergies among bundled ESs were heterogeneous and nonlinear.•There were all-win and zero-sum exceptions of trade-offs among bundled ESs. Understanding the relationships among multiple ecosystem services (ESs) is crucial for the sustainability of natural capital and ESs. The objective of this paper was to explore the antagonistic and synergistic relationships among ESs in their respective ESs bundles (ESBs) from the perspectives of heterogeneity and nonlinearity. Six ESs were quantified using different models, and the relationships among ESs were analysed by combining spatial mapping and statistical methods in the Beijing-Tianjin-Hebei (BTH) urban agglomeration. Our results showed that the spatially concordant supply of regulating services and cultural services decreased from northwest to southeast, whereas the delivery of provisioning services exhibited a distinct spatial pattern and decreased from southeast to northwest in the region. Different combinations of ecosystems provided seven types of ESBs with different compositions and quantities of ESs. The trade-offs and synergies among the ESs in the different ESBs had similarities and differences in both the types of ESs and their intensities. The provisioning service was synergistic with the other ESs in some ESBs, and the relationships among the regulating services and among the regulating services and the cultural service could be antagonistic in other ESBs. Within each ESB, the trade-offs and synergies among the bundled ESs showed spatially heterogeneous changes across the simplified landscapes, and the provision of the involved ESs displayed different nonlinear responses along the productivity gradients. There were different all-win and zero-sum exceptions for the trade-offs involving different ESs in each ESB, with the former indicating the possibilities of mitigating trade-offs and the latter demonstrating the detrimental effects of severe trade-offs. According to our findings, we suggested that the features of ES delivery and their relationships should be considered to ensure the effectiveness, efficiency and equity of the spatially targeted management of natural capital and ESs.